Study of the University Electronic Games E-sports League and Its E-sports Players - Sánta, János (International Journal of Engineering and Management Sciences, 2022)
E-sports are competitive video games coordinated by different leagues and organisations. E-sports players belong to teams or different managements, which are sponsored by various economic companies and establishment. In the beginning, only offline and then online competitions were organised, and nowadays an offline final takes place in sports halls at the end of an online qualification round. The primary objective of the present research is to study the e-athletes participating in the University Electronic Games (UEG) e-sports competition.  In addition to the e-sports players, I consider it important to examine the tournament itself, how the players interviewed rate it and what motivated them to participate again. I conducted an online questionnaire survey among the participants of the three seasons of the UEG online tournament organised by the University of Debrecen. UEG is the largest university e-sport tournament in Hungary in terms of its number of participants, which is why it was selected for the study. The participants in the study are motivated to compete in order to achieve success and enjoy competing to win, for them e-sports is a self-fulfilment. They keep up to date with national e-sports news and competitions through social media and the university mailing system. In general, the participants rate the UEG e-sports championship highly. The organisers need to improve the organisation of the tournament and their preparedness to run a tournament of this size. Their strengths are their helpfulness and their accurate and precise information about the tournament.